Analysing the ‘green’ consumer segment in China – An Empirical Study on ‘green’ characteristics of consumers in Ningbo and Shanghai - Otte, Maren (2009)
This paper analyses the green consumer segment in China with the means of an empirical study on ‗green‘ characteristics of consumers in two of China‘s western cities Ningbo and Shanghai. The methodological approach in this research was constructionist in terms of its ontology, and a combination of interpretivism and positivism with regards to the epistemology. The research tool in my dissertation was a self-completion questionnaire, with a descriptive cross-sectional design. Information was gathered with a 'convenience sample technique' with the means of 122 questionnaires made up out of closed questions. For this study, a non-probability sample was chosen for reasons of feasibility, therefore the findings are not representative for China, and thus have to be used tentatively. A regression and cluster analysis was conducted to find out, which demographic, psychographic and behavioural variables correlate with the dependent variables and to group consumers according to similarities of their environmental attitudes and behaviours. The regression analysis revealed that the psychographic variables had a much higher explanatory power than the demographic variables in profiling the green consumer. Only the socio-economic variables marital status, education and household were significantly correlated with one dependent variable, whereas all psychographic variables ('altruism', 'perceived environmental knowledge'and 'perceived behaviour control') are significantly correlated with at least one or all dependent variables. Furthermore a positive relationship between the dependent variables 'ecologically conscious consumer behaviour', 'environmental concern' and 'attitude towards green products' was found. The cluster analysis generated five distinct groups of Chinese consumers: the 'reluctant green consumers', the 'environmentalists', the 'green consumers', the 'environmental apathetics' and the 'uninformed/ constrained greens'. Notably, all consumer groups showed a relatively high ecologically conscious consumer behaviour but a relatively low perceived behaviour control.